Formation and clearance of active and inactive metabolites of opiates in humans - Aderjan, Rolf; Skopp, Gisela (Therapeutic drug monitoring, 1998)
The results of recent investigations of the analgesic and the nonanalgesic effects of opioid glucuronides are relevant to the research on drug abuse in forensic toxicology. As has been shown for heroin, knowledge of the state of distribution and elimination of active and inactive metabolites and glucuronides offers new possibilities in forensic interpretation of analytic results. Because of similar metabolic degradation, calculation of the time-dependent ratio of the concentration of morphine and its glucuronide metabolites in blood or serum allows a rough estimation of increased dosage and of time elapsed since the last application. Drug effects can be examined with respect to individual case histories, including overdose and survival time if the patient died. However, different methods of administration and the strong influence of different volumes or compartments of distribution of parent compounds and metabolites on concentrations in human body tissues require careful use of glucuronide concentration data. - In Germany, dihydrocodeine (DHC) is prescribed as a heroin substitute, and relative overdoses are needed to be effective. DHC metabolism was studied in three patients who died from overdoses. All metabolites (dihydrocodeine-6-glucuronide[DHC6], nor-DHC [NDHC], dihydromorphine [DHM], nor-DHM [NDHM], and DHM-3-and 6-glucuronide [DHM3G, DHM6G]) were determined using HPLC and fluorescence detection. Concentrations of DHM (0.16 mg/L to 0.22 mg/L serum) were found. The DHM glucuronide ratios were similar to those of morphine. Receptor binding studies showed that the binding affinity of DHM to porcine µ-receptor was higher than that of morphine, and DHM6G's binding affinity was as high as that of morphine-6-glucuronide (M6G). Metabolites may play an important role in the effectiveness of DHC in substitution and toxicity. Because of enzyme polymorphism, the formation of DHC poses a risk for proper dosage in patients who are either poor or extensive metabolizers. The distribution of opioid glucuronide in cerebral spinal fluid in relation to transcellular transport in central nervous tissue is discussed with respect to the receptor binding of opiates and drug effect.
Gesehen am 15.08.2023